Індукція стійкості до іонів міді і кадмію мультирезистентних штамів роду Pseudomonas - Янєва, О.Д.; Смирнова, Г.Ф.; Підгорський, В.С. (Видавничий дім "Академперіодика" НАН України, 2007)
Induction of the resistance to copper and cadmium ions in three multiresistant Pseudomonas strains has been studied. Pre-treatment of the strains with low concentrations of cadmium and copper resulted in the increased metal tolerance in strains A03 and C25a, i.e. a shorter mean generation time compared to the control. No cross-induction was observed for any strain. The protein synthesis de novo is essential for the copper resistance in the studied strains, while the cadmium resistance is determined by other factors.